Comparison of marginal accuracy in two different materials used in provisional crown & bridge – an in vitro experimental study - Javed, Faizan; Arif, Aysha; Raza Khan, Farhan (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the difference in the marginal accuracy at buccal, lingual, mesial and distal margins of temporary crowns fabricated with bisacryl-based temporary crown material. Method: The in-vitro, experimental, laboratory-based study was conducted at the Aga Khan University, Karachi, from September to December 2019, and comprised two bisacryl-based temporary crown material, Integrity and Protemp 4, which were used to fabricate a sample of 24 temporary crowns. A pre-operative polyvinyl siloxane impression served as a template for temporary crown fabrication. A right mandibular molar tooth on a typodont was prepared to receive a crown. The provisional crown material was syringed onto the template and was allowed to cure. All four surfaces of the crown were observed under a stereomicroscope equipped with digital single-lens reflex camera at 25.6x magnification. An image of each surface was captured and a photographic record was maintained. An image processing software was used for the measurement of marginal discrepancy. Marginal accuracy among the four surfaces was assessed. Data was analysed using SPSS 23. Results: Mean marginal discrepancy for provisional crowns fabricated with Protemp 4 and Integrity was 410±222um and 319±176um, respectively. The marginal discrepancy between the two groups was statistically significant (p=0.027), with buccal margin exhibiting the most discrepancy (p<0.01). Conclusions: Integrity showed less microleakage than Protemp 4. Among all the walls, the buccal wall showed the most microleakage. Marginal accuracy was found to be dependent upon the type of provisional crown material and the side of the prepared axial wall. Key Words: Crowns, Dental marginal adaptation, Tooth preparation, Dental materials.